Implicit response incompatibility slowed down asymptomatic individuals with Alzheimer's disease pathology: Biomarkers (non‐neuroimaging) / Novel biomarkers. (7th December 2020) - Hung, Shao‐Min; Wu, Daw‐An; Harrington, Michael G; Shimojo, Shinsuke; Arakaki, Xianghong
Abstract: Background: Alzheimer patients exhibit explicit decline of cognitive abilities. However, such decline, by definition, does not appear pre‐symptomatically. Here we introduced a subliminal incompatibility paradigm where a masked word was either congruent or incongruent to the response to the subsequent target stimulus. We examined if implicit response incompatibility led to performance decline in asymptomatic individuals with Alzheimer's disease pathology, serving as a possible early marker of the disease. Method: Cognitively healthy (CH) participants (demographically matched) were recruited from the local community, consisting of two subgroups based on cerebrospinal fluid (CSF) proteins: with normal amyloid/tau ratio (CH‐NAT, n = 20) or pathological amyloid/tau ratio (CH‐PAT, pre‐symptomatic AD, n = 20). A task‐switching Stroop task was implemented. Each trial contained two stimuli, and participants had to name the color or word of a colored word for each stimulus with button press. If the two stimuli involved different task demands (e.g. color naming and word naming), it was a switching trial. Otherwise it was a non‐switching trial. In‐between the two stimuli, a forward‐ and backward‐masked word congruent (i.e. same button press) or incongruent to the response to the subsequent stimulus was inserted. Result: Final analysis included only the trials with both stimuli correctly responded. On average, participants had near‐ceiling performance with ∼95% accuracy. In a mixed ANOVA with one between‐subject factor (CH‐PAT/CH‐NAT) and three within‐subject factors (word/color naming, switching or non‐switching, and masked word congruent or incongruent), we analyzed the reaction time of the target (second) stimulus. We found significant main effects of word/color and switching. That is, participants responded significantly slower (1) to color of the stimulus (typical Stroop effect) and (2) when they had to switch attention across different stimulus features in a trial (color to word or vice versa). Critically there was an interaction between switching and congruency. Further analysis showed that during switching, incongruent trials slowed down significantly. Such effect was only evident in CH‐PATs ( p = 0.00005), but not CH‐NATs ( p = 0.1). Conclusion: During a challenging task‐switching condition, the behavioral performance of asymptomatic individuals with Alzheimer's disease pathology was significantly affected by implicit response incompatibility.